Social capital and the transition to democracy - Bădescu, Gabriel, 1969-; Uslaner, Eric M. (Routledge, 2003)
This edited collection presents the latest quantitative research on how post-communist countries are adapting to Western models of society.
Keywords: Democratization -- Europe, Eastern.; Democratization -- Europe, Central.; Democratization -- Former Soviet republics.; Social capital (Sociology) -- Europe, Eastern.; Social capital (Sociology) -- Europe, Central.; Social capital (Sociology) -- Former Soviet republics.; Démocratisation -- Europe de l'Est.; Démocratisation -- Europe centrale.; Démocratisation -- Ex-URSS.; Capital social (Sociologie) -- Europe de l'Est.; Capital social (Sociologie) -- Europe centrale.; Capital social (Sociologie) -- Ex-URSS.; POLITICAL SCIENCE -- Political Process -- General.; Democratization; Social capital (Sociology); Central Europe; Eastern Europe; Soviet Union -- Former Soviet republics